2019
DOI: 10.1037/cfp0000117
|View full text |Cite
|
Sign up to set email alerts
|

Is it the sex, the romance, or the living together? The differential impact of past sexual, romantic, and cohabitation histories on current relationship functioning.

Abstract: Before their current relationship, individuals may have had a variety of previous relationships such as romantic relationships, sexual relationships, and cohabiting relationships. In this study we explored the common or shared influence of these 3 types of previous relationships, and the unique influence of each type, on current relationship functioning. With a sample of more than 4,000 individuals we found that there was a significantly negative shared influence for previous romantic, sexual, and cohabiting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…It could well be that those who were having more casual sex had attitudes that were less supportive of commitment in relationships or they were less able to sustain relationships. Some research has indicated that the total number of sexual partners was associated with negative attitudes about relationships and both variables were associated with relationship instability (Busby et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It could well be that those who were having more casual sex had attitudes that were less supportive of commitment in relationships or they were less able to sustain relationships. Some research has indicated that the total number of sexual partners was associated with negative attitudes about relationships and both variables were associated with relationship instability (Busby et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For many, there are different levels of expectations and purposes between cohabiting and marriage as well as an incongruence with the construct of marriage which can make the choice to live together more appealing. Busby et al (2019) determined further risk in the lack of conversation, as well as the casualness of dating and sex within partnerships, which were more often affiliated with cohabiting than with marriage. Horowitz et al (2019) looked at levels of trust and satisfaction amongst partnerships determining that these factors are higher for married versus cohabiting relationships; they found 74% of those married versus 58% of those cohabiting believe their partner has their best interest, and that 68% of those married believe their partner always tells the truth versus 54% of those cohabiting.…”
Section: Risks Of Cohabitingmentioning
confidence: 99%
“…Factors that often influence the decision to live together included sexual satisfaction, relationship satisfaction, commitment, relationship stability, relationship attitudes, and communication (Busby et al, 2019 ). These elements of a relationship are recommended to be at the forefront for discussion before officially moving in together, however it is very possible for people to move in without any consideration or conversation of any of these issues.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations